Distribution of the pattern, incidence, and determinants of sexually transmitted infections among patients attending Adari Hospital, Hawassa City, Sidama Region, Ethiopia - Melese Birmeka; Damtew Bekele (PAGEPress Publications, 2024)
Sexually Transmitted Infections (STIs) cause serious medical and psychological health problems in Ethiopia and vary in different localities. Thus, this study aimed to investigate patterns, status, and the association of sexually transmitted infections and local risk factors in the patients attending Adari Hospital. An institutional-based cross-sectional study was carried out from September 2021 to June 2022. Systematic simple random sampling was used to select a total of 385 patients. In addition, five years of retrospective data were collected. Data were collected through blood tests, urethral and vaginal discharge swabs, structured questionnaires, interviews, and observations. Variables with p-values less than 5% are considered as significant. The overall prevalence of sexually transmitted infections was 74.4%. The odds of STIs in patients who were urban, single, presence of two and above sexual partners, illiterate, sexual intercourse without using a condom, and sex after drinking alcohol and chewing khat were more likely to be infected with STIs as compared with their counterparts. STIs were highly prevalent and one of the health challenges of Hawassa city.